The impact of relationship marketing tactics on customer loyalty in Malaysian telecommunication industry / Afif Haikal Hanifa - Hanifa, Afif Haikal (Faculty of Business Management, 2017)
The purpose of this study is to identify on the impact of relationship marketing tactics on customer loyalty within Malaysian telecommunication industry where its competitive environment is very crucial. Companies in Malaysian telecommunication industry were executing variety of relationship marketing tactics in order to achieve high level of customer loyalty. Four relationship marketing tactics were adopted for this study which is service quality, price perception, brand image and value offers to be examined their impact on customer loyalty. The population for this study is customers of telecommunication service providers in Bandaraya Melaka. A total of 150 sets of questionnaires were distributed and only 120 were returned. Results from data analysis are based on SPSS version 20. Quantitative type of data was used for the purpose of the study. The finding from this research shows that there are significant and positive relationship between relationship marketing tactics and customer loyalty. The result shows that value offered has the strongest impact on customer loyalty.